Advance care planning for nursing home residents with dementia: Influence of 'we DECide' on policy and practice. Issue 1 (January 2017) - Ampe, Sophie; Sevenants, Aline; Smets, Tinne; Declercq, Anja; Van Audenhove, Chantal
Highlights: Advance care planning is essential in the case of dementia. Shared decision-making is best suited for discussing advance care planning. 'We DECide' is a training in shared decision-making for advance care planning. 'We DECide' had a positive impact on advance care planning policy, not on practice. Implementing advance care planning requires involvement of the whole organization. Abstract: Objectives: (1) To pilot 'we DECide' in terms of influence on advance care planning policy and practice in nursing home dementia care units. (2) To investigate barriers and facilitators for implementing 'we DECide'. Methods: This was a pre-test—post-test study in 18 nursing homes. Measurements included: compliance with best practice of advance care planning policy (ACP-audit); advance care planning practice (ACP criteria: degree to which advance care planning was discussed, and OPTION scale: degree of involvement of residents and families in conversations). Results: Advance care planning policy was significantly more compliant with best practice after 'we DECide'; policy in the control group was not. Advance care planning was not discussed more frequently, nor were residents and families involved to a higher degree in conversations after 'we DECide'. Barriers to realizing advance care planning included staff's limited responsibilities; facilitators included support by management staff, and involvement of the whole organization. Conclusion: 'We DECide' had a positive influence on advance care planning policy. Daily practice, however, did not change. Future studies should pay more attention to long-term implementation strategies. Practice implications: Long-term implementation of advance care planning requires involvement of the whole organization and a continuing support system for health care professionals.